Dexamethasone accelerates degradation of aryl hydrocarbon receptor (AHR) and suppresses CYP1A1 induction in placental JEG-3 cell line - Stejskalova, Lucie; Rulcova, Alice; Vrzal, Radim; Dvorak, Zdenek; Pavek, Petr (Toxicology letters, 2013)
The JEG-3 choriocarcinoma cell line has been proposed as a model cell line of human placental trophoblast for induction studies via aryl hydrocarbon receptor (AHR). We examined whether glucocorticoid dexamethasone influences AHR-mediated induction of CYP1A1 enzyme in the JEG-3 cell line. We found that dexamethasone dose- and time-dependently suppresses CYP1A1 transactivation in gene reporter assays, CYP1A1 mRNA induction, and upregulation of 7-ethoxyresorufin-O-deethylase (EROD) activity by 3-methylcholanthrene (MC) and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in JEG-3 cells. Co-transfection of JEG-3 cells with glucocorticoid receptor (GR) expression construct and treatment with dexamethasone abolished the effect of MC on CYP1A1 promoter construct in transient transfection gene reporter assays. RU486, a GR antagonist, suppressed the effect of dexamethasone on MC-induced transactivation of AHR responsive reporter constructs. We also found that dexamethasone stimulates both ligand-dependent and ligand-independent degradation of AHR but not of aryl hydrocarbon receptor nuclear translocator (ARNT) protein in JEG-3 cells. In experiments with proteasome inhibitors MG132 and bortezomib, we found that the degradation is not sensitive to proteasome inhibition in JEG-3. We can conclude that dexamethasone suppresses AHR-mediated CYP1A1 induction in JEG-3 cells through the unique mechanism of AHR-GR crosstalk, which involves accelerated degradation of AHR.
Keywords: messenger RNA; Transcriptional Activation; nádorové buněčné linie; Dose-Response Relationship, Drug; Glucocorticoid receptor; vztah mezi dávkou a účinkem léčiva; Up-Regulation; Methylcholanthrene; receptory aromatických uhlovodíků - jaderný translokátor; těhotenství; upregulace; Glucocorticoids; Aryl hydrocarbon receptor; reportérové geny; Aryl Hydrocarbon Receptor Nuclear Translocator; placenta; Polychlorinated Dibenzodioxins; Receptors, Aryl Hydrocarbon; Receptor Cross-Talk; Choriocarcinoma cell line; Proteasome; glukokortikoidy; cytochrom P-450 CYP1A1; Cell Line, Tumor; Placenta; Receptors, Glucocorticoid; MG132; Genes, Reporter; interakce mezi receptory a ligandy; ženské pohlaví; RNA, Messenger; Humans; Pregnancy; dexamethason; aktivace transkripce; methylcholanthren; CYP1A1; Dexamethasone; polychlorované dibenzodioxiny; receptory aromatických uhlovodíků; receptory glukokortikoidů; Female; lidé; Cytochrome P-450 CYP1A1